Trade policy lobbying in the European Union: Who captures whom? - Cornelia Woll (Max Planck Institute for the Study of Societies, 2006)
What role do firms play in the making of EU trade policy? This article surveys the policy domain and lays out the instruments firms can employ to influence decisions on trade. It underlines that European trade policy is characterized by a high degree of institutional complexity, which firms have to manage in order to be successful. In particular, the European Commission works intensively to solicit business input in order to gain bargaining leverage vis-à-vis third countries and the EU member states. This reverse lobbying creates a two-channel logic of trade policy lobbying in the EU. Corporate actors have a very good chance of working closely with the European Commission if they can propose pan-European trade policy solutions. This can be either trade liberalization or EU-wide regulatory restrictions on trade. Demands for traditional protectionist measures, especially those that reveal national interest divergences, are difficult to defend at the supranational level. Protectionist lobbying therefore goes through the national route, with corporate actors working to block liberalization by affecting the consensus in the Council of Ministers. The chapter illustrates this two-channel logic by studying business-government interactions in agricultural trade, textiles and clothing, financial services, and telecommunication services. – – Welchen Einfluss haben Unternehmen auf die europäische Handelspolitik? Durch einen Überblick des Politikfelds analysiert der Artikel Instrumente, mit denen Unternehmen in der EU Lobbyismus betreiben können. Vielen Firmen werden allerdings nicht von sich aus aktiv. Im Gegenteil, die Europäische Kommission bemüht sich aktiv um die Zusammenarbeit der Unternehmen, da sie dadurch ihre Verhandlungsposition vis-à-vis Mitgliedsstaaten und Drittstaaten stärken kann. Dieses umgekehrte Lobbying hat Folgen für die Inhalte der Unternehmensforderungen im Bereich Handelspolitik. Wirtschaftliche Akteure können ein gutes Arbeitsverhältnis mit der Europäischen Kommission aufbauen, wenn sie gesamteuropäische Konzepte verfolgen, sei es Handelsliberalisierung oder EU-weite Regulierung. Nationaler Protektionismus kann europäische Entscheidungsfindung blockieren, so dass merkantilistische Anfragen an die nationalen Regierungen gerichtet werden müssen, die diese dann durch den Rat der Minister voranbringen können. Der Artikel illustriert diese zweigleisige Lobbyingstrategien in der Landwirtschaft, dem Textilhandel, dem Finanzdienstleistungssektor und der Telekommunikation.
Keywords: 300